Synthesis of (Z,Z)-1,2-dihydroxyimino-3,6-diamino-8,9-O,O-cyclopentylidenenonane-8,9-diol and its complexes with copper(II), nickel(II), cobalt(II) and uranyl(VI) - Sekerci, M (Marcel Dekker Inc, 2000)
The new vic-dioxime ligand,(Z,Z)-1,2-dihydroxyimino-3,6-diamino-8,9-O,O-cylopentylidenenonane-8,9-diol (LH2) was synthesized by treating 1,3-diamino-5,6-O,O-cylopentylidenehexane-5,6-diol (R-NH2) with anti-chloroglyoxime in the presence of a base, e.g. triethylamine. vic-Dioximes have been found to be in the Z,Z-form according to H-1 NMR and C-13 NMR data. Mononuclear complexes having a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II) and Ni(II) salts. However, the metal-ligand ratio and structure of the UO2(VI) complex was found to be 1:1 and dinuclear. The ligand and its complexes were characterized by magnetic susseptibility, elemental analyses, IR, UV-Vis., H-1 NMR,C-13 NMR, TGA and DTA studies. Structures for the complexes are suggested.
Keywords: Unsymmetrical Vic-Dioximes; Crown-Ether Moieties; Dioxouranium(Vi) Complexes; Schiff-Bases; Palladium(Ii); Platinum(Ii); (E,E)-Dioximes; Ligands